The Influence of Internal Factors on Stock Prices: Cross-Sector Empirical Evidence in the Indonesian Capital Market - Mukhsin, Muhammad; Lukiana, Ninik; Suyono, Aji Prasetyo (International Journal of Accounting and Management Research, 2026)
This study aims to examine the effect of internal factors on stock prices in the Indonesian capital market. The problem arises because previous studies on the role of profitability, leverage, and company size in determining market valuation still show inconsistent results. Using a quantitative approach, this study employs multiple linear regression analysis on 985 observations of companies from the financial, primary consumer, and technology sectors. The independent variables tested include ROE, DER, company size, and sector dummy variables, with stock prices as the dependent variable. The results of the analysis show that ROE and DER have a negative effect on stock prices, while company size has a significant positive effect. In addition, the primary consumer and technology sectors have higher stock prices than the financial sector as a reference. The conclusion of this study confirms that profitability is not always a positive signal for investors, while large company size reflects trust and stability. These findings contribute to the literature on the relationship between internal factors and stock prices, while also offering practical implications for investors and company management in investment decision-making.